Genome‐wide association studies for growth‐related traits in a crossbreed pig population. (29th December 2020) - Xue, Y.; Li, C.; Duan, D.; Wang, M.; Han, X.; Wang, K.; Qiao, R.; Li, X.‐J.; Li, X.‐L.
Summary: Growth‐related traits are important economic traits in the pig industry that directly influence pork production efficiency. To detect quantitative trait loci and candidate genes affecting growth traits, genome‐wide association studies were performed for backfat thickness (BF) and loin muscle depth (LMD) in 370 Chuying‐black pigs using Illumina PorcineSNP50 BeadChip array. We totally identified 14 BF‐associated SNPs, which included 11 genome‐wide SNPs ( P  < 1.39E‐06) and 3 chromosome‐wide suggestive SNPs ( P  < 2.79E‐05) and for LMD, 9 SNPs surpassed the genome‐wide significant threshold ( P  < 1.39E‐06). These SNPs explained 30.33 and 27.51% phenotypic variance for BF and LMD respectively. Furthermore, 14 and 9 genes nearest to the significant SNPs were selected to be candidate genes, including MAGED1, GPHN, CCSER1, and GUCY2D for BF and PARM1, COL18A1, HSF5, and SCML2 genes for LMD. One significant SNP, which explained 6.07% of phenotypic variance for BF, mapped to a pleiotropic quantitative trait locus with a 494‐kb interval. Together, the SNPs and candidate genes identified in this study will advance our understanding of the complex genetic architecture of BF and LMD traits, and they will also provide important clues for future implementation of a genomic selection program in Chuying‐black pigs.